Microbe-assisted seedling crop improvement by a seaweed extract to address fucalean forest restoration - Malfatti, Francesca; Kaleb, Sara; Saidi, Amira; Pallavicini, Alberto; Agostini, Laura; Gionechetti, Fabrizia; Natale, Sara; Balestra, Cecilia; Bevilacqua, Stanislao; Falace, Annalisa (Frontiers in Marine Science, 2023)
In the Mediterranean, Cystoseira sensu lato (s.l.) (Phaeophyceae) forests have sharply declined and restoration measures are needed to compensate for the loss. Assisted regeneration through the outplanting of seedlings grown ex-situ has proven to be a sustainable option. Optimizing mesocosm culture can maximize survival of the most critical embryonic stages and reduce long-term maintenance costs. Host-microbiome interactions could also play a crucial role in seedling development and welfare. In this context, we aimed to advance a cultivation protocol that stimulates the growth and fitness of Ericaria amentacea (Phaeophyceae) seedlings and identify the associated microbial biofilm communities. Seedlings were cultured in 6 treatments [i.e., filtered seawater (SW, C, Control), von Stoch-enriched SW (VS), VS + algal extract (VSA), algal extract-enriched SW: A1< A2< A3]. After the field, A2 seedlings had the highest cover (1372 ±53.66 mm2), which was 1.8 and 1.9 times greater than in VS and VSA, respectively. The addition of the algal extract and nutrients significantly affected the structure and composition of the microbial community that shifted over time in each culture medium. We identified a treatment-specific microbial fingerprint. After the mesocosm phase, A2 was characterized by 4 unique taxa: Postechiella, Winogradskyella, Roseovarius and Arenibacter (Bacteria). Given the success of A2 seedlings, we propose the probiotic consortia candidates characterized by the unique treatment-taxa in conjunction with the shared taxon Psychroserpens (Bacteria, present in A1, A2, VSA, VS) and the reminder community. Within the holobiont concept, the effect of algal extract or nutrients on the algae and/or biofilm could have important consequences for tuning the overall interaction networks. Our study has shown that macroalgal restoration could benefit from both the use of commercial algal extract and tailored nutrient enrichment in ex-situ cultures and the identification of probiotic consortia candidates that promote seedling growth.